Seamus Heaney and the emblems of hope - Moloney, Karen Marguerite, 1951- (University of Missouri Press, 2007)
"Explores Seamus Heaney's adaptation of the Celtic ritual known as the Feis of Tara, demonstrates the sovereignty motif's continued relevance in works by Irish poets Thomas Kinsella, John Montague, Eavan Boland, and Nuala Ni Dhomhnaill, and refutes criticism that charges sexism and overemphasizes sacrifice in Heaney's poetry"--Provided by publisher.